Find the derivative of the function f(x)=-3(2-9x)^(1/4)

I have:

f'(x)=-3[1/4(2-9x)(-9)]+0(2-9x)^(1/4)

=-3[-9/4(2-9x)]

=-3(81/4x-9/2)

=-243/4x+27/2

Did I do that right?

3 posts
• Page **1** of **1**

Find the derivative of the function f(x)=-3(2-9x)^(1/4)

I have:

f'(x)=-3[1/4(2-9x)(-9)]+0(2-9x)^(1/4)

=-3[-9/4(2-9x)]

=-3(81/4x-9/2)

=-243/4x+27/2

Did I do that right?

I have:

f'(x)=-3[1/4(2-9x)(-9)]+0(2-9x)^(1/4)

=-3[-9/4(2-9x)]

=-3(81/4x-9/2)

=-243/4x+27/2

Did I do that right?

- Cafe au lait
**Posts:**6**Joined:**Mon Jan 03, 2011 11:02 pm

Cafe au lait wrote:Find the derivative of the function f(x)=-3(2-9x)^(1/4)

I have:

f'(x)=-3[1/4(2-9x)(-9)]+0(2-9x)^(1/4)

When you took the 1/4 power down front, what should have been left behind as the power on the parenthetical?

- nona.m.nona
**Posts:**250**Joined:**Sun Dec 14, 2008 11:07 pm

Lol I redid it without the product rule and that made it a lot easier! I know I got it right now, thanks!

- Cafe au lait
**Posts:**6**Joined:**Mon Jan 03, 2011 11:02 pm

3 posts
• Page **1** of **1**